HVDC electricity transportation technology: feasibility study (Algeria) - Nedjem Eddine Benchouia; Mohammed Saaidia; Lekhmissi Derardjia (My University, 2020)
HVDC technology is gradually becoming a standard in electrical energy transportation. Even more, in some situations, it’s the best practical solution. The research work presented hereafter is dedicated to the exploration of the basic notions, the induced gains, the basic components, the basic and extended structures, the applications, and the real implemented projects of such technology. An overview of the research works concerned with the challenges of this expandable technology and an economic study of the deployment of real electrical transportation lines and their feasibility in Algeria are presented.